Factor Analysis of Patient with Hypertension on Self-Regulation Based on Self-Belief - Riza Fikriana (Journal of Global Pharma Technology, 2019)
Objective: The purpose of this study was to analyze the factors that influence self-regulation based on the self-beliefs of hypertension patients. Methods: The design of the study used observational analytics with a cross-sectional study approach. The sample size consisted of 108 patients with hypertension in health centers in Malang Regency, East Java, Indonesia. The independent variables were physical activity, food consumption, medication adherence, control in health care and stress management. The dependent variable was self-regulation. Data were collected using a questionnaire tested for validity and reliability. Logistic regression was used to analyze the results. Results: Age (p = 0.014) and support of health workers (p = 0.004) had an effect on the self-regulation of food consumption. Age (p = 0.008), gender (p = 0.006), family history (p = 0.004), family support (p = 0.014) and health insurance (p = 0.028) had an effect on the self-regulation of medication adherence. Age (p = 0.022) affected the self-regulation of control to health services. Peer support (p = 0.008) was significantly associated with stress management. Conclusion: The consolidation of social support and health services is important to improve self-regulation based on self-beliefs in patients with hypertension.Keywords: Self-regulation, Confidence, Hypertension.